Identifying Situated Cognition in Organizations - Elsbach, Kimberly D.; Barr, Pamela S.; Hargadon, Andrew B. (Organization Science, 2005)
Using the established definition of situated cognition in organizations as “the interaction of cognitive schemas and organizational context” (Lant 2002), we examine empirical case studies from the last 15 years to illustrate what situated cognitions in organizations might actually look like. Grounded in this research, we develop a framework that identifies how some specific forms of cognitive schemas (i.e., rule schemas, event schemas, person schemas) and specific contexts (e.g., physical contexts, institutional contexts) interact during sensemaking processes to give rise to momentary perceptions that we call situated cognitions. We present evidence that common patterns of interaction between schemas and context may occur during sensemaking in organizations. In terms of theoretical implications, our framework focuses attention on the specific interactions between context and cognition (rather than on context or cognition alone) that comprise situated cognitions, and helps to more concretely define situated cognitions as momentary or temporally bounded perceptions. We offer several practical implications of this framework for managers and suggest avenues for further elaboration on our ideas through research.